Optimizing TPACK in Learning in the Digital Era: Systematic Literature Review - Dian Marisa; Ida Rindaningsih (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to explore the optimization of the Technological Pedagogical Content Knowledge (TPACK) framework in learning within the digital era using a Systematic Literature Review (SLR) approach. TPACK is a concept that integrates technology, pedagogy, and content knowledge as the foundation for developing learning strategies relevant to current needs. With the increasing role of technology in education, it is crucial to understand how TPACK can be effectively implemented to improve the quality of learning. This article analyzes a number of published studies within a specific timeframe to identify trends, challenges, and best practices in TPACK implementation. The findings indicate that optimizing TPACK requires a synergy between technological expertise, innovative teaching strategies, and content adaptation tailored to the learning context. Furthermore, professional teacher development and institutional support are key factors in the successful implementation of TPACK. This study provides valuable insights for educators, policymakers, and researchers to develop more effective learning models in the digital era while addressing existing challenges. Thus, optimizing TPACK can serve as a strategic step toward creating adaptive and sustainable learning.